KARAKTER FENOTIPIK SAPI BETINA PERANAKAN ONGOLE (PO) KEBUMEN - Pita Sudrajad; Subiharta Subiharta (Widyariset, 2014)
Kebumen regency is designated as a village breeding centre for Ongole Grade cattle in Indonesia. Therefore, phenotypic characterization of 1,190 Ongole grade cows (1–6 years old) was conducted in Kebumen Regency. The study indicated that the average body measurement of Ongole Grade cows in Kebumen was higher and longer than the standard national body measurement set by National Standard Performance of Indonesia 7356:2008. Dominant qualitative characters of Ongole Grade cows in Kebumen was white coat colour, black muzzle, red or black vulva, straight trilateral head shape, with long horns, loose skin, and well-developed hump. Related to the potential of the Ongole Grade cow in Kebumen, efforts are needed in order to maintain the purity and the sustainability that is appropriate with agro-ecosystem and preferences of local farmers.